Copper-mediated direct thiolation of aryl C–H bonds with disulfides. Issue 29 (15th July 2019) - Deng, Ke-Zuan; Zhang, Li-Li; Chen, Ye-Feng; Xie, He-Xin; Xu, Xiao-Bo; Xia, Cheng-Cai; Ji, Ya-Fei
Abstract : A directing group-assisted copper-mediated thiolation of aromatic amides with disulfides via direct C(sp 2 )–H activation has been developed. Abstract : An efficient copper-mediated ortho -C(sp 2 )–H thiolation of aromatic amides directed by a novel directing group [4-chloro-2-(1 H -pyrazol-1-yl)phenyl]amine has been developed without the need of other additives or oxidants, allowing for an increased usefulness. With the high compatibility of sterically demanding substrates, this reaction is scalable and can tolerate a wide scope of functional groups to provide alkyl and aryl thioethers in good to excellent yields (up to 93%). Furthermore, the protocol has been successfully implemented for the selenylation as well.